2018
DOI: 10.1016/j.ecoenv.2017.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the effects of putrescine and spermidine pre-treatment on cadmium stress in wheat

Abstract: In several cases a correlation was found between polyamines and abiotic stress tolerance. However, the individual polyamines may have different effects, which also vary depending on the type of treatment. When applied as seed soaking or added hydroponically 0.5mM putrescine and spermidine, different changes were induced during 50µM cadmium stress in wheat plants. Seed-soaked plants were exposed to cadmium immediately after germination for 5 days, while plants pre-treated with polyamines hydroponically were str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 43 publications
6
39
0
Order By: Relevance
“…Under cadmium- and copper-induced oxidative stress, lipid peroxidation in sunflower leaf discs increased, while the activities of glutathione reductase (GR) and superoxide dismutase (SOD) decreased (Groppa et al, 2001). When plants were treated with exogenous PAs (1 mM), Spm treatment reduced the effects of Cd 2+ and Cu 2+ on lipid peroxidation almost to control values (Tajti et al, 2018). In addition, GR activity was completely restored by Spm or Spd treatments, and SOD activity under Cu 2+ treatment was restored by Spm treatment (Table 3).…”
Section: Polyamines and Abiotic Stress Responsesmentioning
confidence: 99%
“…Under cadmium- and copper-induced oxidative stress, lipid peroxidation in sunflower leaf discs increased, while the activities of glutathione reductase (GR) and superoxide dismutase (SOD) decreased (Groppa et al, 2001). When plants were treated with exogenous PAs (1 mM), Spm treatment reduced the effects of Cd 2+ and Cu 2+ on lipid peroxidation almost to control values (Tajti et al, 2018). In addition, GR activity was completely restored by Spm or Spd treatments, and SOD activity under Cu 2+ treatment was restored by Spm treatment (Table 3).…”
Section: Polyamines and Abiotic Stress Responsesmentioning
confidence: 99%
“…Many reports suggest that SA treatment influence PA content in plants [131,161]. Recently, Tajti et al [162] studied the role of putrescine and spermidine on wheat under Cd stress and also reported increased levels of SA in those plants; however, the exact mechanism involved in SA-mediated HM stress tolerance and the relationship between PA and SA in plants are still unknown.…”
Section: Polyaminesmentioning
confidence: 99%
“…Treatment of Trigonella seeds with 5mM putrescine before exposing to temperature stress degrees removed the harmful effects induced by temperature stress on the measured yield parameters (Figure 1). Exogenous application of polyamines stimulates tolerance to high or low temperatures in various crop plants (Perez-Amador et al, 2002;Tajti et al, 2018). It was found that putrescine improves the yield and quality of bell pepper (Mahmood et al, 2017) and broccoli (Zheng et al, 2019).…”
Section: Resultsmentioning
confidence: 99%